“The Law of the Earth in Opposition to the Asphalt” Popular Religiosity, Historical Continuities and Rural Mentalities Between the Victory Populators 1957-1990; [“La Ley de la Tierra en Oposición Al Asfalto” Religiosidad Popular, Continuidades Históricas y Mentalidades Rurales Entre Los Pobladores de la Victoria 1957-1990] - Garin-Abarzua, E (Universidad de Santiago de Chile, 2019)
This article attempts to approach popular religiosities as an expression of historical and identity continuity of the “pobladores de La Victoria” in relation to their old rural habitat. Our hypothesis of this article questions the constitution of an eminently urban identity of “pobladores” in their attempts to join the city. In that sense and from a perspective focused on the “ethic of earth” we intend to associate the popular religiosity of the “pobladores of La Victoria” as a cultural expression of “longue duree” highly attached to the identity collection of these social actors. © 2019, Universidad de Santiago de Chile. All rights reserved.